2015
DOI: 10.1002/nbm.3381
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and effect of tissue composition on cerebellar γ-aminobutyric acid (GABA) MRS in an elderly population

Abstract: Magnetic resonance spectroscopy (MRS) provides a valuable tool to non-invasively detect brain gamma-amino butyric acid (GABA) in vivo. GABAergic dysfunction has been observed in the aging cerebellum. Studying cerebellar GABA changes is of considerable interest in understanding certain age-related motor disorders. However, little is known about the reproducibility of GABA MRS in an aged population. Therefore, this study aimed to explore the feasibility and reproducibility of GABA MRS in the aged cerebellum at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 70 publications
3
19
0
Order By: Relevance
“…The whole-dataset CV reported in this study falls well within the range of inter-individual CVs observed for edited GABA+ measurements in the literature: 6–24% (Bogner et al, 2010; Evans et al, 2010; Geramita et al, 2011; Long et al, 2015; Mikkelsen et al, 2016a; O’Gorman et al, 2011). That a majority of the total variance in the data was participant-level variance indicates that initial steps taken to standardize acquisition parameters across vendors (most notably TR, TE and editing pulse bandwidth) were largely successful.…”
Section: Discussionsupporting
confidence: 87%
“…The whole-dataset CV reported in this study falls well within the range of inter-individual CVs observed for edited GABA+ measurements in the literature: 6–24% (Bogner et al, 2010; Evans et al, 2010; Geramita et al, 2011; Long et al, 2015; Mikkelsen et al, 2016a; O’Gorman et al, 2011). That a majority of the total variance in the data was participant-level variance indicates that initial steps taken to standardize acquisition parameters across vendors (most notably TR, TE and editing pulse bandwidth) were largely successful.…”
Section: Discussionsupporting
confidence: 87%
“…Most previous studies evaluated the MEGA‐PRESS sequence for quantification of GABA, Glu, Gln, and Glx or GABA only . Two studies quantified Glx by JPRESS .…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies evaluated the MEGA-PRESS sequence for quantification of GABA, Glu, Gln, and Glx or GABA only. [10][11][12][13][14][15][16][17][18] Two studies quantified Glx by JPRESS. 36,37 CV evaluation for test-retest reliability has been applied extensively to all sequences in several investigations, as for MEGA-PRESS 16 and JPRESS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations